(untitled) (Dhaka University Journal of Science, 2019)
In this paper, it has been examined the effect of preceding birth interval on nutritional status in the form of Stunting of the children aged under 5 years of age in Bangladesh.For the purpose of the analysis, Bangladesh Demographic and Health Survey (BDHS), 2014 data has been used. The study cases are the children under 5 years aged born during last delivery of their mother. The response variable is Nutritional Status of under 5 year children in the form of stunting. The key independent variables is the length of the preceding birth interval, measured as the number of months between the births of the child under study.Bivariate analysis along with a Chi-square test has been performed to examine the association between preceding birth interval and stunting of the children. To determine the effect of preceding birth interval, three different logistic regression models (Model-I: considering only the preceding birth intervals, Model-II: covariate of model-I along with demographic and socioeconomic factors and Model-III: covariates of model-II along with health related factors) were considered. The occurrence of stunting has been found to be inversely related with the preceding birth interval for the children aged under 5 years in Bangladesh. This inverse association has been found statistically significant for three models.After adjusting the demographic, socio-economic and health-related factors, the OR (odds ratio) shows that the percentage of being stunted is 73% higher for the children whose preceding birth interval is less than 24 (<24) while it is 37% higher for the children whose preceding birth interval is between months compared to whose birth interval is more than 60 (60>) months with 99% confidence interval (1.27, 2.36)***and (1.07, 1.45)***respectively. Dhaka Univ. J. Sci. 67(2): 139-144, 2019 (July)